DEVELOPMENT OF SPECTROPHOTOMETRIC METHODS FOR SIMULTANEOUS DETERMINATION OF ARTESUNATE AND CURCUMIN IN LIPOSOMAL FORMULATION - Sharma, Sarvesh; Saraogi, Gaurav K.; Kumar, Vimal (International Journal of Applied Pharmaceutics, 2015)
The present study is very expectant towards the development of co-encapsulated liposomal formulation. The assay method for artesunate has a challenge because it doesnot have a readily recognisable absorption chromophore needed for UV spectroscopy. Curcumin, a lipid soluble antioxidant, exhibits solvent and medium sensitive absorption and fluorescence properties. A simple and rapid method involving two reaction steps has been developed for assay of artesunate and curcumin combination in liposomal formulation. Stock solution of artesunate and curcumin were diluted to final concentration of 10 µg/ml. The UV scan of 10 µg/ml solution of artesunate and curcumin combinations showed the absorbtion maxima at 240 nm and 425 nm respectively. The coloured complex obeyed the Beer's law in the concentration range of 2-20 µg/ml. The above methods is rapid tool for routine analysis of artesunate and curcumin in novel carrier system. The recovery studies confirmed the accuracy and precision of the methods. Keywords: Artesunate, Curcumin, Liposomal .